Calidad del servicio y su influencia en la satisfacción de los clientes de Inversiones y Servicios Magia - Iquitos, año 2021 - Gálvez Malaverry, Brianda Elizabeth (2022)
The main objective of the study is to determine the relationship between the two. The quality of the service and its impact on customer satisfaction of magic of investment and service - Iquitos, 2021, therefore, belongs to the study an application that describes the level of correlation and non-experimental design is that Taking as an example the investments and services of the company to Magia's clients in relation to data collection, questionnaires are used as a tool, technology is exploration. The questions are ordered with Likert scales. Ratings appear sometimes, never, often, almost always, always with claims in information processing Using Microsoft Excel, the results are presented in tables and graphs. After data processing in Excel and SPSS v-25. The document concludes that the indicators of this study strongly correlated with the variables analyzed. One of the best ways to be competitive and stay in the market is to build long-term relationships with customers through great service. Quality services must also be combined with high-quality products. surprises and exceeds customer expectations. Today, customer satisfaction is the goal organizations have a basis for better customer response.